Social News Site: People’s Interest and Content Spreading - Vardya, Rizka; Nurhajati, Lestari (Journal of Communication and Public Relations, 2022)
The background of this research is the presence of Social News Site in Indonesia. Contents could be viral as long as it is being shared. People will read the information if they are interested or if it is useful for them. This research aims to find out the people’s interest of content on Social News Site and its spread. There are several factors that build the people’s interest in consuming information. This research uses descriptive qualitative research method with data collection technique through interviews, online observation and literature study. This study focuses to analyze people’s interest and content spreading. The researcher uses AISAS (Sugiyama & Andree, 2010) model to analyze this problem. AISAS stands to Attention, Interest, Search, Action, and Share.